Mengulik Kompleksitas Proses Difusi Inovasi Teknologi di Perpustakaan - Endang Fatmawati (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2018)
Innovation is a certain idea, practice or product that is realized and accepted as something new to be adopted. Adoption is a process from getting acquainted with an innovation to decide to accept or reject. There is an innovation category that is sustaining and discontinues. An indication that there has been an innovation acceptance process is that it appears in behavioral, cognitive, affective and psychomotor changes.